America First? A US-centric view of global capital flows - Peter McQuade; Martin Schmitz (European Central Bank (ECB), 2019)
Both academic researchers and policymakers posit a unique role for the US in the inter-national financial system. This paper investigates the characteristics and determinants of US cross-border financial flows and examines how these contrast with those of the rest of the world. We analyse the relative importance of US, country-specific, and global variables as determinants of aggregate and bilateral US financial flows and as determinants of country-level cross-border financial flows excluding those directly involving the US. Our results indicate that variation in US variables - notably the VIX and US dollar exchange rate - has a quantitatively important influence on global financial flows, but mostly via US cross-border flows. Global and national risk indicators perform better in explaining "rest of the world" flows. Moreover, we find that the correlation between US and rest of the world flows peaks in periods of elevated uncertainty. We interpret our findings as evidence for the existence of a global financial cycle, only some of which is driven by policies and events in the US.
Keywords: F15; F21; F36; F42; G15; 330; International capital flows; US financial system; VIX; US dollar exchange rate; monetary policy spillovers